Efektifitas Promosi Berbasis WhatsApp Dalam Pemasaran Minuman Honeymon - Pratiwi Putri Lestari; Putri Rizky; Dedi Simanjuntak; Zainal; Sukmawati; Rika Silvany; Resti Ayu Ningrum (Cattleya Darmaya Fortuna, 2026)
By utilizing existing social media, it is possible to promote and see consumer enthusiasm for the products being sold. In promoting the product, the business owner can create their own advertisements by making videos showing the process of producing Honeymon drinks, starting from the packaging process, sticker application, and the handover process from the Honeymon drink owner to cafes and sales stalls in several locations in Binjai City. They also provide articles about the health benefits of consuming Honeymoon drinks. Sales using social media can assess customer satisfaction through testimonials sent by consumers. Based on observations within a month of using social media, Honeymoon drink sales have increased, because the number of social media followers has also increased, making it easier to promote Honeymoon drinks.